2022
DOI: 10.1051/0004-6361/202141970
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of zirconium in the globular cluster 47 Tucanae: a possible Zr–Na correlation?

Abstract: We determined abundances of Na and Zr in the atmospheres of 237 RGB stars in Galactic globular cluster (GGC) 47 Tuc (NGC 104), with a primary objective of investigating possible differences between the abundances of Zr in the first generation (1P) and second generation (2P) stars. For the abundance analysis, we used archival UVES/GIRAFFE spectra obtained during three different observing programmes. Abundances were determined from two Na I and three Zr I lines, using 1D hydrostatic ATLAS9 model atmospheres. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Some other studies have shown tentative signs for a possible correlation between the abundances of light and s-process elements in other Type I GGCs, such as signatures for Sr-Na and Y-Na relations in M 4 (Spite et al 2016;Villanova & Geisler 2011; but see also D'Orazi et al 2013). In addition, our recent analysis of Zr abundance in 237 RGB stars in 47 Tuc suggests the existence of weak but statistically significant Na-Zr correlation and 2P-1P Zr abundance difference of ∆[Zr/Fe] 2P−1P ≈ 0.06 (Kolomiecas et al 2021). The existence of such correlations would indicate that the light and s-process elements should have been produced in the same polluters that have enriched the 2P stars in some elements and depleted in others.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…Some other studies have shown tentative signs for a possible correlation between the abundances of light and s-process elements in other Type I GGCs, such as signatures for Sr-Na and Y-Na relations in M 4 (Spite et al 2016;Villanova & Geisler 2011; but see also D'Orazi et al 2013). In addition, our recent analysis of Zr abundance in 237 RGB stars in 47 Tuc suggests the existence of weak but statistically significant Na-Zr correlation and 2P-1P Zr abundance difference of ∆[Zr/Fe] 2P−1P ≈ 0.06 (Kolomiecas et al 2021). The existence of such correlations would indicate that the light and s-process elements should have been produced in the same polluters that have enriched the 2P stars in some elements and depleted in others.…”
Section: Introductionmentioning
confidence: 80%
“…We also note that no Ba-Na correlation was detected by D' Orazi et al (2010) in their analysis of 110 RGB stars in 47 Tuc, which indirectly supports our assertion that the [Ba/Fe] − [Na/Fe] anti-correlation detected in our study is, in fact, spurious. This said, it would be nevertheless interesting to see whether the Ba-Na -or any correlation between any other s-process and light elements -could be seen in other GGCs, especially given the tentative detection of Zr-Na correlation in the RGB stars of 47 Tuc that is suggested in the analysis of Kolomiecas et al (2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations